Strengthening Mechanisms in Carbon Nanotubes Reinforced Metal Matrix Composites: A Review - Íris Carneiro; Sónia Simões (Metals, 2021)
Carbon nanotubes (CNTs)-reinforced metal matrix composites are very attractive advanced nanocomposites due to their potential unusual combination of excellent properties. These nanocomposites can be produced by several techniques, the most reported being powder metallurgy, electrochemical routes, and stir or ultrasonic casting. However, the final mechanical properties are often lower than expected. This can be attributed to a lack of understanding concerning the strengthening mechanisms that act to improve the mechanical properties of the metal matrix via the presence of the CNTs. The dispersion of the CNTs is the main challenge in the production of the nanocomposites, and is independent of the production technique used. This review describes the strengthening mechanism that act in CNT-reinforced metal matrix nanocomposites, such as the load transfer, grain refinement or texture strengthening, second phase, and strain hardening. However, other mechanisms can occur, such as solid solution strengthening, and these depend on the metal matrix used to produce the nanocomposites. Different metallic matrices and different production techniques are described to evaluate their influence on the reinforcement of these nanocomposites.